PENGUJIAN EFISIENSI BENTUK SETENGAH KUAT DI INDONESIA - Sri Lestari Kurniawati; Wiwik Lestari (STIE Perbanas Surabaya, 2011)
Efficient market is the market in which when there is an announcement the market get a reac- tion quickly from the investors. This finally influences the price movement of securities to- ward the new equilibrium price. Some of action dealing with announcement and that it is be- lieved to have trustable information, this information can be considered feasible to get re- sponse technically so as to influence the transaction in the capital market outside. Further- more, a market can be efficient also when it is a strong form and the security prices fully ex- presses all information widespread. This study attempts to find out to what extend the effi- ciency for capital market information in Indonesia by testing some actions done by the com- panies announced on the stock split, reverse split, profit announcement, and dividend shar- ing. The sample was taken by means of purposive sampling. Each consists of 26 samples of events for stock split and 19 sample of event for stock reverse. For announcement of the profit consists of 28 companies with 45 events and dividend announcement 26 companies for 52 events. The Expected is calculated using 3 models (Market Model, Mean Adjusted Model, and Market Adjusted Model). Using estimation period of 100 with five day observation pe- riod after event analysis, it shows that Indonesia capital markets has different reactions to- ward each event. In general, the results show that only profit announcement is responded by the capital market.